STUDY OF VLADIMIR PROPP'S NARRATIVE STRUCTURE IN LE FANTÔME DE L'OPÉRA NOVEL BY GASTON LEROUX - Khoirunnisa, Adelia Defa (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study aims to examine the actions of the characters in the novel Le Fantôme de l'Opéra by Gaston Leroux and their involvement in the story using aspects of narrative structure contained in Vladimir Propp's narrative structure study. This research uses qualitative approach and narrative approach. The material object of this research is Gaston Leroux’s Le Fantôme de l'Opéra which is studied using the concept of narrative structure proposed by Vladimir Propp. The data collection techniques used are reading and note-taking techniques. The data are grouped in a data tabulation table and then analyzed using structural analysis techniques. The results of this study show that this novel consists of 25 functions namely trickery, villainy, mediation, interdiction, beginning counteraction, unrecognized, reconnaissance, difficult task, delivery, the donor, complicity, transfiguration, struggle, absentation, hero’s reaction, departure, pursuit, provision, spatial translocation, the initial misfortune, violation, rescue, solution, return, exposure. The five spheres are villain, donor, helper, dispatcher, hero. The scheme in this novel is divided into three parts, namely the beginning, middle and end. These three schemes form a plot, namely a mixed plot, because the events that occur in this story begin in the middle. While the story progresses forward and several times displays pieces of flashback sections that explain the background of the story. Therefore, it can be concluded that the aspects of narrative structure found in this novel are aspects of actor's function, spheres of action and schemes, then the relationship between aspects is found in the aspect of the schemes.